Project Management of Energy Conservation for construction firms - Бутник, Д. В. (Eastern-European Journal of Enterprise Technologies, 2012)
A system for preparing and implementing measures necessary for the improvement and development of the production process and implementation of energy conservation measures in the construction industry companies hes been developed